Diseminácia a prezívanie zárodkov endoparazitov v zivotnom prostredí - Juris, P; Breza, M; Schmidtová, D; Venglovský, J (Veterinarni medicina, 1991)
Pig farms with the annual capacity from five to 20 thousand head represent one of the crucial fields of agriculture influencing the environment in the CSFR. Daily production of large amounts of liquid excrements (150-300 m3), as a result of high concentrations of animals, poses not only technical but also sanitary problems closely related to the animal and man's health. In a long-term (267 days) field study the authors followed the development and survival of eggs of the model helminth Ascaris suum, contamination of the environment with the propagative stages of pig enteronematodes and possibility of their devitalization in a mechanico-chemico-biological waste-water treatment plant. Eggs of A. suum placed in the soil to the depth of 10 to 60 cm in November (1987) did not develop in winter months. Their development continued in spring months--at soil temperatures of 8.6 degrees C (at 5 cm depth) or 8.9 degrees C (at 20 cm depth). The embryonated eggs were found out at the beginning of the 20th decade of the experiment (May, 1988). The most positive samples on the investigated pig farm were found out in the vicinity of the central reservoir for waste water, showing the presence of both unembryonated and embryonated eggs of A. suum and Trichuris suis, with sporadic occurrence of Oesophagostomum dentatum L3 larvae. As demonstrated by our results, the tested waste-water treatment system complies only with the requirements of water management--with respect to the absence of the endoparasite propagative stages in the treated water.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Soil; Animal Husbandry; Swine; Ascaris; Animals; prasata; počet parazitárních vajíček; chov zvířat; zvířata; Parasite Egg Count; půda